Effects of glacial melting on physiological performance of Macrocystis pyrifera in the Fjord of the Mountains, Magellanic Sub-Antarctic ecoregion, Chile - Coral-Santacruz, Diana; Mendez, Fabio; Marambio, Johanna; Haye, Pilar A.; Bahamonde, Francisco; Mansilla, Andres (My University, 2024)
The Magellanic Sub-Antarctic ecoregion (MSE) was covered by ice during the Last Glacial Maximum (21,000 years ago), with the ice masses advancing and retreating throughout the Quaternary. Currently, this ecoregion supports a significant number of endemic species and a high diversity of macroalgae. However, anthropogenic climate change has accelerated global warming, exacerbating glacier melt over the last decade. In this study, we evaluated the effect of glacial melting on the ecophysiology of Macrocystis pyrifera, a brown macroalga that forms underwater forests and is considered a foundation species susceptible to environmental change. Tissue samples were collected from apical and basal fronds of young individuals from three M. pyrifera populations located in the Fjord of the Mountains (51 degrees 10'53 '' S-73 degrees 17'08 '' W). We found significant differences in maximum relative electron transport rate (rETR(max)), electron transport efficiency (Alpha), and light saturation point (E-k) between apical and basal fronds, as well as between sites influenced by glacial-melt (high turbidity, low temperature, and low salinity) versus those with minimal or no glacial influence (low turbidity, high temperature, and high salinity). Pigment concentrations (chlorophyll-a, chlorophyll-c, and fucoxanthin) did not show significant variation between fronds and sites, except under extreme conditions. Our results indicate that photosynthetic response differs between sites affected by glacial melt and those unaffected. Apical fronds demonstrated higher photosynthetic efficiency in response to environmental fluctuations. This study offers valuable insights into how M. pyrifera adjusts its photosynthetic performance in response to varying conditions driven by glacial-melt, thereby enhancing our understanding of how kelp forests might locally respond to climate change.
Keywords: magellan region; glacier melt; macrocystis pyrifera; photosynthesis performance